Gas Hydrate Accumulation Related to Pockmarks and Faults in the Zhongjiannan Basin, South China Sea - Zhang, Guangxu; Wang, Xiujuan; Li, Lin; Sun, Luyi; Guo, Yiqun; Lu, Yintao; Li, Wei; Wang, Zhaoqi; Qian, Jin; Yang, Taotao; Wang, Wenlong (Frontiers in Earth Science, 2022)
The amplitude and coherence attributes of three-dimensional (3D) seismic data are used to confirm gas hydrate occurrence and to delineate its distribution in the Zhongjiannan basin, South China Sea. High amplitude anomalies (HAAs) are distributed above or below the regional base of gas hydrate stability zone (BGHSZ), which intersect with the bottom simulating reflectors (BSRs) or are interrupted by different types of pockmarks. The maximum amplitude attribute extracted along T1 (5.5 Ma) horizon is controlled by the widely distributed faults. The layer-bound polygonal faults (PFs) show networks of small normal faults and the dominant orientations of PFs are similar or orthogonal to the regional tectonic faults, which provide the fluid migration pathways for gas and fluids to form HAAs. BSR shows the strong amplitude and continuous reflection where the faults or PFs can reach the BGHSZ without the influence of the pockmarks. Most of the pockmarks are related with the reactivation of faults and magmation, and some pockmarks are caused by the dissociation of gas hydrate. Around the matured pockmark, the BSR is discontinuous, and HAAs locally appear within the pockmarks. The inverted acoustic impedance profile shows obviously high values of HAAs except in pockmark zones. Partial HAAs occur above BGHSZ and the continuity is interrupted by the pockmarks with only high values around the pockmarks. We propose that BSR, HAAs, pockmarks, and different types of faults are closely related with the occurrence and distribution of gas hydrates in the study area. This work allows us to understand the relationship between gas hydrate occurrence and accumulation with pockmarks, faults and magmatic activities.